The influence of bronchial asthma on physical health, activities, and emotional health of asthmatic children and their parents: reliability and validity of the Malaysian version of CHSA / Maryam S E Hussein - S E Hussein, Maryam (2015)
There are various developed instruments to assess impact of asthma among asthmatic children but few of these instruments were developed in paired versions of child and caregiver. Children Health Survey for Asthma is one of the instruments that have paired versions, parent version (CHSA) (item, n = 48) and child version (CHSA-C) (item, n = 25). The aims of the present study were to establish the validity and reliability of the Malaysian versions of M-CHSA and M-CHSA-C, to assess the effect of asthma on Malaysian asthmatic children and their parents, to present the difference of child’s and parent’s report about the effect of asthma on their lives, and to investigate the differences, effects and relationships of socio-demographic and medical data with the health outcomes from asthmatic children and their parents. Questionnaires were translated to Bahasa Malaysia using previously established international guidelines. Data from 180 pairs of asthmatic children (7-16 years old) and their parents were analyzed using two method; Classical method where Internal consistency reliability was determined using Cronbach’s alpha, and construct validity was determined by factor analysis (IBM SPSS version 20), and modem test theory based on Rasch-Model analysis (Bond & Fox steps software). Wilcoxon Signed-ranks test was used to test the difference between children’s and parents’ reports on the effect of asthma on their lives. Mann-Whitney Test, Kruskal-Wallis test, correlation analysis, multiple linear regression, ANCOVA, and logistic regression were used to investigate the differences, effects and relationships between socio-demographic data and domains, and correlation between domains themselves for the asthmatic children and their parents. The results showed that both reliability and factor analysis reveal an acceptable reliability and a good construct validity of the scales. And the reliability of both translated questionnaires were further supported by a strong and moderate correlation between the scores on the initial and the repeat administration of M-CHSA and M-CHSA-C. All items measures for both translated questionnaires are fitted to Rasch-Model. These results showed that the translated questionnaires have good reliability and validity for research purpose. The results showed that the highest score in family’s activities domain for parent version while in child version were highest score in the child’s activity domain. Also, there were significant differences between child’s and parent’s report in child’s physical health and child’s emotional health. There were significant differences in child’s activity in different smoking home environment, level of child’s education, and asthma duration. Also, there were significant differences in child’s emotional health with different parent’s gender, parent’s age, and parent’s ethnicity. There was significant difference in child’s physical health with different travelling time. There were significant negative weak correlation between child’s activity and child’s age and asthma duration, and between child’s emotional health and asthma duration. There were significant positive moderate correlations between all domains. Asthma duration and monthly income were the predictors for child’s emotional health. Monthly income for the family affected child’s emotional health while ethnicity affected family’s activity. Finally, child’s emotional health in non-smoking home environment was 4.055 times better than in smoking home environment. The evidences presented in this study supported the idea that numerous factors such as socio-demographic factors are capable of influencing HRQoL of asthmatic children and their parents. These types of studies are important for successful medical care for asthmatic children.